Penerapan Aplikasi Pelayanan Masyarakat Desa (Studi Kasus: Desa Tonggara Kecamatan Kedungbanteng Kabupaten Tegal) - Aang Alim Murtopo; Zaenul Arif; Bangkit Indarmawan Nugroho; Nugroho Adhi Santoso; Sarif Surorejo; Bayu Aji Santoso; Syefudin; Gunawan; Wresti Andriani; Rifki Dwi Kurniawan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The implementation of the Community Service Application in Tonggara Village, Kedungbanteng District, Tegal Regency aims to simplify and speed up the community service process. This application is web-based and can be accessed by the public via computer, smartphone or tablet devices. Some of the services available in this application include providing information about village profiles, village potential, and village programs. The Village Community Services Application can process various village administration services, such as domicile certificates, business certificates and trade business permits. The Village Community Services Application provides a platform for the community to submit complaints to the village government, providing consultation services for the community regarding various matters, such as health, education and law. The implementation of this application is expected to increase the effectiveness and efficiency of community services in Tonggara Village. Apart from that, this application is also expected to increase the transparency and accountability of the village government to the community. The benefits of implementing the Village Community Service Application in Tonggara Village have several benefits, including increasing the effectiveness and efficiency of community services, making the community service process faster, easier and more transparent. Increasing transparency and accountability of village governments, communities can easily access information about available services and monitor village government performance. Increasing community satisfaction, people feel more satisfied with the services provided by the village government. Increasing community participation, it is easier to get involved in village activities. Implementing the community service application in Tonggara Village is the right step to improve the quality of public services in the village. This application can help village governments to provide more effective, efficient, transparent and accountable services to the community.